DEVELOPMENT OF THE FOREIGN ECONOMIC ACTIVITY OF THE ENTERPRISE: ASPECTS OF MARKETING STRATEGIES AND ECONOMIC SECURITY - ZAKRYZHEVSKA, Iryna; OSTAPCHUK, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The publication examines the issues of development of foreign economic activity of business entities, the benchmarks of which are the increase in the volume of production and export of products (goods, works, services), the expansion of market share in foreign markets, the improvement of the systems of goods movement and distribution of products, the increase in the volume of income and export revenue, increasing profitability and increasing capitalization, strengthening internal financial and economic and resource potential for further expansion into domestic and foreign sales markets. It is shown that in accordance with the identified tasks, two blocks of tasks are important: (1) increasing production capacities and (2) using effective marketing tools in order to consolidate and strengthen the positions of enterprises in foreign sales markets. Therefore, the subject of this study was the strategic aspects of the company's marketing activity in the sales markets.At the same time, it is shown that active foreign economic activity requires significant investments and is characterized by a high level of uncertainty, and, therefore, requires sufficient attention to the issue of economic security. That is why the purpose of the research is to substantiate the elements of strategizing, as well as tools and means of marketing support, including guaranteeing the economic security of relevant processes, programs and projects for the development of the enterprise's foreign economic activity.The practical significance of the results of the publication lies in the approbation of the obtained results by domestic business entities in order to increase the volume and efficiency of their foreign economic activities. The scientific novelty of the obtained results lies in the further development of the theoretical and applied provisions of the coordination of the policy of the development of the foreign economic security of the enterprise and ensuring the economic security of such processes.
Keywords: enterprise; business entity; enterprise management; business economics; foreign economic activity; development; strategizing; marketing; marketing support tools; marketing strategies; risks and threats; development security; economic security; sustainability; export